Conditioned comfort: A multi-scalar analysis of residential heat adaptation in the tropical city-state of Singapore - Sarah Hian May Chan; Joshua Dao-Wei Sim; Natalia Borzino; Yunjing Li; Khant Min Naing; Pearl Min Sze Tan; Yi Xuan Tay; Flora Yuting Du; Samuel Chong Wei Chng; Jason Kai Wei Lee; Kai Zheng; Harvey Neo (Urban Climate, 2026)

Outdoor artificial light at night exposure and risk of myopia: A cross-sectional and prospective cohort study among Hong Kong children - Yingan Li; Yuzhou Zhang; Ka Wai Kam; Yuhan Cui; Poemen Chan; Patrick Ip; Wei Zhang; Alvin Young; Chi Pui Pang; Clement C. Tham; Li Jia Chen; Mei Po Kwan; et al. (Environmental Research, 2026)

Long-distance migrations of catfishes in two large tropical rivers: The Ayeyarwady and Mekong rivers - An V. Vu; Lee J. Baumgartner; John Conallin; Zau Lunn; Nyein Chan; Ian G. Cowx; Martin Mallen-Cooper; Gregory S. Doran; Bronwyn M. Gillanders; Jason D. Thiem; Cameron M. Kewish; Karin Limburg (Fisheries Research, 2025)

Immunomodulatory activities of aqueous extracts of Dendrobium officinale and Dendrobium nobile in peripheral blood mononuclear cells of tongue cancer patients - Grace Gar-Lee Yue; Si Gao; Leanne Lee Leung; Jian Xu; Hongwen Li; Jason Ying-Kuen Chan; Clara Bik-San Lau (Phytochemistry Letters, 2025)

Establishment and characterization of a novel patient-derived TP63-rearranged anaplastic large-cell lymphoma model PTCL-S1 - Kelila Xin Ye Chai; Elizabeth Chun Yong Lee; Zhimei Li; Nur Ayuni Binte Muhammad; Jing Quan Lim; Dachuan Huang; Soon Thye Lim; Jason Yongsheng Chan; Choon Kiat Ong (Human Cell, 2025)
Anaplastic large-cell lymphoma (ALCL) accounts for 15% of all peripheral T-cell lymphomas globally and can be further divided into subcategories, of which patients with ALK-negative ALCL have dismal prognosis and overall survival. We established a patient-derived xenograft (PDX) and in vitro model (designated PTCL-S1) of TP63 -rearranged ALK-negative ALCL from the primary tumour site of a 55-year old Chinese woman. Whole genome sequencing of the patient’s tumour identified various mutations including AKT1 and NOTCH1 , as well as the TP63 - TBL1XR1 gene fusion. RNA sequencing followed by Sanger sequencing confirmed the gene rearrangement in original tumour, PDX and PTCL-S1 cell line. Immunohistochemistry profiling of the PDX model and cell-line were consistent with the patient’s primary tumour sample (CD3 + /CD30 + /CD79a-). Cytotoxic agents (doxorubicin, etoposide and gemcitabine) commonly used in ALCL treatment exhibited potent anti-proliferative activity in the cell-line. In conclusion, the established PTCL-S1 cell line can be a useful tool for further investigation of the understanding of TP63 -rearranged ALK-negative ALCL.

Contaminants and residues have varied distributions in large volumes of wheat - Sheryl A. Tittlemier; Richard Blagden; Jason Chan; Dainna Drul; Don Gaba; Mei Huang; Anja Richter; Mike Roscoe; Maria Serda; Valentina Timofeiev; Michael Tran (Food Additives & Contaminants: Part A, 2025)

Current practices for QSP model assessment: an IQ consortium survey - Jason R. Chan; Richard Allen; Britton Boras; Antonio Cabal; Valeriu Damian; Francis D. Gibbons; Abhishek Gulati; Iraj Hosseini; Jeffrey D. Kearns; Ryuta Saito; Lourdes Cucurull-Sanchez; Jangir Selimkhanov; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Relation of preconception eating behaviours to dietary pattern trajectories and gestational weight gain from preconception to late pregnancy - Jason Loh; See Ling Loy; Geeta Appannah; Marjorelee T. Colega; Keith M. Godfrey; Fabian Yap; Yap Seng Chong; Johan G. Eriksson; Jerry K.Y. Chan; Shiao-yng Chan; Mary F.F. Chong; Jun S. Lai (Appetite, 2024)

Establishment and characterization of a patient-derived solitary fibrous tumor/hemangiopericytoma cell line model - Jing Yi Lee; Peiyong Guan; Abner Herbert Lim; Zexi Guo; Zhimei Li; Jessica Sook Ting Kok; Elizabeth Chun Yong Lee; Boon Yee Lim; Bavani Kannan; Jui Wan Loh; Cedric Chuan-Young Ng; Kah Suan Lim; et al. (Human Cell, 2023)

Diverging fates of cadmium and glyphosate during pasta cooking - Sheryl A. Tittlemier; Lianna Bestvater; Jason Chan; Valentina Timofeiev; Anja Richter; Kun Wang; Yuefeng Ruan; Marta Izydorczyk; Bin Xiao Fu (Food Additives & Contaminants: Part A, 2023)

Campus node-based wastewater surveillance enables COVID-19 case localization and confirms lower SARS-CoV-2 burden relative to the surrounding community - Jangwoo Lee; Nicole Acosta; Barbara J. Waddell; Kristine Du; Kevin Xiang; Jennifer Van Doorn; Kashtin Low; Maria A. Bautista; Janine McCalder; Xiaotian Dai; Xuewen Lu; Thierry Chekouo; et al. (Water Research, 2023)

Multi-omic profiling and real time ex vivo modelling of imatinib-resistant dermatofibrosarcoma protuberans with fibrosarcomatous transformation - Jason Yongsheng Chan; Elizabeth Chun Yong Lee; Zhimei Li; Jing Yi Lee; Abner Herbert Lim; Eileen Poon (Human Cell, 2023)

Mini-PBPK-Based Population Model and Covariate Analysis to Assess the Complex Pharmacokinetics and Pharmacodynamics of RO7449135, an Anti-KLK5/KLK7 Bispecific Antibody in Cynomolgus Monkeys - Hao Cai; Xun Tao; Jeongsup Shim; Rebecca N. Bauer; Meire Bremer; Wei Bu; Jason LaMar; Rachel Basile; Edward Dere; Tien Nguyen; Steven Laing; Pamela Chan; et al. (The AAPS Journal, 2023)

Occurrence and stability of PCMX in water environments and its removal by municipal wastewater treatment processes - Chun-Kit Au; K.K. Jason Chan; Wan Chan; Xiangru Zhang (Journal of Hazardous Materials, 2023)

The photometric observation of the quasi-simultaneous mutual eclipse and occultation between Europa and Ganymede on 22 August 2021 - Chu Wing So; Godfrey Ho Ching Luk; Giann On Ching Chung; Po Kin Leung; Kenneith Ho Keung Hui; Jack Lap Chung Cheung; Ka Wo Chan; Edwin Lok Hei Yuen; Lawrence Wai Kwan Lee; Patrick Kai Ip Lau; Gloria Wing Shan Cheung; Prince Chun Lam Chan; et al. (Icarus, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Significance of Beta-Band Oscillations in Autism Spectrum Disorders During Motor Response Inhibition Tasks: A MEG Study - Vera Moliadze; Alla Brodski-Guerniero; Magdalena Schuetz; Julia Siemann; Ekaterina Lyzhko; Sabine Schlitt; Janina Kitzerow; Anne Langer; Jochen Kaiser; Marcus J. Naumer; Michael Wibral; Jason Chan; et al. (Brain Topography, 2020)
In Autism Spectrum Disorders (ASD), impaired response inhibition and lack of adaptation are hypothesized to underlie core ASD symptoms, such as social communication and repetitive, stereotyped behavior. Thus, the aim of the present study was to compare neural correlates of inhibition, post-error adaptation, and reaction time variability in ASD and neuro-typical control (NTC) participants by investigating possible differences in error-related changes of oscillatory MEG activity. Twelve male NTC (mean age 20.3 ± 3.7) and fourteen male patients with ASD (mean age 17.8 ± 2.9) were included in the analysis. Subjects with ASD showed increased error-related reaction time variability. MEG analysis revealed decreased beta power in the ASD group in comparison to the NTC group over the centro-parietal channels in both, the pre-stimulus and post-response interval. In the ASD group, mean centro-parietal beta power negatively correlated with dimensional autism symptoms. In both groups, false alarms were followed by an early increase in temporo-frontal theta to alpha power; and by a later decrease in alpha to beta power at central and posterior sensors. Single trial correlations were additionally studied in the ASD group, who showed a positive correlation of pre-stimulus beta power with post-response theta, alpha, and beta power, particularly after hit trials. On a broader scale, the results deliver important insights into top-down control deficits that may relate to core symptoms observed in ASD.

A multi-year survey of mycotoxins and ergosterol in Canadian oats - Sheryl A. Tittlemier; Richard Blagden; Jason Chan; Mike Roscoe; Kerri Pleskach (Mycotoxin Research, 2020)

Therapeutic Efficacy of Subcutaneous and Intraperitoneal Injections of a Single Dose of Human Umbilical Mesenchymal Stem Cells in Acute and Chronic Colitis in a Mouse Model - Yu-Lung Chang; Huei-Yu Lo; Shun-Ping Cheng; Kuo-Ting Chang; Xiu-Fang Lin; Sheng-Ping Lee; Jason Ma; Ming-Ling Kuo; Ming-Fa Hsieh; Chin-Kan Chan (Journal of Medical and Biological Engineering, 2020)

Video Education on Hereditary Breast and Ovarian Cancer (HBOC) for Physicians: an Interventional Study - Bhuma Krishnamachari; Mahin Rehman; Jason E. Cohn; Vivian Chan; Neil Modi; Ofri Leitner; Kelly Tangney; April O’Connor; William Blazey; Sharon Koehler; David Tegay (Journal of Cancer Education, 2018)

Mechanical and Clinical Evaluation of a Shape Memory Alloy and Conventional Struts in a Flexible Scoliotic Brace - Wing-Yu Chan; Joanne Yip; Kit-Lun Yick; Sun-Pui Ng; Lu Lu; Kenneth Man-Chee Cheung; Kenny Yat-Hong Kwan; Jason Pui-Yin Cheung; Kelvin Wai-Kwok Yeung; Chi-Yung Tse (Annals of Biomedical Engineering, 2018)

Molecular serum signature of treatment resistant depression - Tillmann Ruland; Man K. Chan; Pawel Stocki; Laura Grosse; Matthias Rothermundt; Jason D. Cooper; Volker Arolt; Sabine Bahn (Psychopharmacology, 2016)

Liposome size and charge optimization for intraarterial delivery to gliomas - Shailendra Joshi; Johann R. N. Cooke; Darren K. W. Chan; Jason A. Ellis; Shaolie S. Hossain; Rajinder P. Singh-Moon; Mei Wang; Irving J. Bigio; Jeffrey N. Bruce; Robert M. Straubinger (Drug Delivery and Translational Research, 2016)

Physician Risk Assessment Knowledge Regarding BRCA Genetics Testing - Jason Cohn; William Blazey; David Tegay; Brian Harper; Sharon Koehler; Brookshield Laurent; Vivian Chan; Min-Kyung Jung; Bhuma Krishnamachari (Journal of Cancer Education, 2015)

Resveratrol prevents pathological but not physiological cardiac hypertrophy - Vernon W. Dolinsky; Carrie-Lynn M. Soltys; Kyle J. Rogan; Anita Y. M. Chan; Jeevan Nagendran; Shaohua Wang; Jason R. B. Dyck (Journal of Molecular Medicine, 2015)

Proof-of-concept randomized controlled trial of pregnenolone in schizophrenia - Christine E. Marx; Jimmy Lee; Mythily Subramaniam; Attilio Rapisarda; Dianne C. T. Bautista; Edwin Chan; Jason D. Kilts; Robert W. Buchanan; Eu Pui Wai; Swapna Verma; Kang Sim; Jayaraman Hariram; et al. (Psychopharmacology, 2014)

The effects of attentional load on saccadic task switching - Jason L. Chan; Joseph F. X. DeSouza (Experimental Brain Research, 2013)

Single laboratory evaluation of a planar waveguide-based system for a simple simultaneous analysis of four mycotoxins in wheat - Sheryl A. Tittlemier; Mike Roscoe; Dainna Drul; Richard Blagden; Colleen Kobialka; Jason Chan; Don Gaba (Mycotoxin Research, 2013)

The muscarinic M1 receptor positive allosteric modulator PQCA improves cognitive measures in rat, cynomolgus macaque, and rhesus macaque - Jason M. Uslaner; Donnie Eddins; Vanita Puri; Christopher E. Cannon; Jane Sutcliffe; Chan Sing Chew; Michelle Pearson; Jeffrey A. Vivian; Ronald K. Chang; William J. Ray; Scott D. Kuduk; Marion Wittmann (Psychopharmacology, 2013)

Comparative mapping in watermelon [Citrullus lanatus (Thunb.) Matsum. et Nakai] - Katherine Sandlin; Jason Prothro; Adam Heesacker; Nelly Khalilian; Rebecca Okashah; Wenwen Xiang; Eleni Bachlava; David G. Caldwell; Chris A. Taylor; Danelle K. Seymour; Victoria White; Eva Chan; et al. (Theoretical and Applied Genetics, 2012)

Gender-specific modulation of immune system complement gene expression in marine medaka Oryzias melastigma following dietary exposure of BDE-47 - Roy R. Ye; Elva N. Y. Lei; Michael H. W. Lam; Alice K. Y. Chan; Jun Bo; Jason P. van de Merwe; Amy C. C. Fong; Michael M. S. Yang; J. S. Lee; Helmut E. Segner; Chris K. C. Wong; Rudolf S. S. Wu; et al. (Environmental Science and Pollution Research, 2012)

Phosphatidylcholine metabolism in human endothelial cells: modulation by phosphocholine - Jason T. Wong; Monroe Chan; Douglas Lee; Jenny Yan Jiang; Monika Skrzypczak; Patrick C. Choy (Molecular and Cellular Biochemistry, 2000)